A Study on the Factors Influencing the Happiness of Rural Elderly - Soukanya, Bounthot; Xie, Lee Wen (Indonesian Journal of Advanced Research, 2025)
This study aimed to investigate the relationship between social support and life satisfaction among 200 rural elderly individuals using the "Social Support Rating Scale" and the "Life Satisfaction Rating Scale." Through independent sample t-tests and correlation analysis, the results revealed significant differences in subjective support across dimensions such as age, economic status, and marital status. Objective support also showed significant variations in gender, age, economic status, and marital status. The utilization of support differed significantly by age. Additionally, life satisfaction among rural elderly exhibited notable differences in gender, age, economic status, and marital status. Significant positive correlations were found between all dimensions of social support (and total scores) and life satisfaction. The findings suggest that enhancing psychological care and social support for rural elderly can improve their life satisfaction.